1994
DOI: 10.1007/s001250050085
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage by the glycation products of glyceraldehyde 3-phosphate and lysine

Abstract: In order to evaluate whether base modifications, apurinic/apyrimidinic site formation, strand breaks, or a combination of these lesions results from the interaction of glycation products with DNA, plasmid DNA was first reacted with these products, and then subjected to digestion with endonuclease III and endonuclease IV of Escherichia coli. Analysis of the differential effects of digestions with these enzymes by electrophoresis on agarose gels demonstrated that reactive glycation products produce both base mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Although it is not yet clear how excessive entry of glucose or lipid elicits beta-cell injury, increased non-enzymatic glycation of cellular proteins has been identified in animal studies [58,59]. The presence of HNE-modified proteins suggests that oxidative stress with lipid peroxidation also contributes to islet-cell injury [60].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not yet clear how excessive entry of glucose or lipid elicits beta-cell injury, increased non-enzymatic glycation of cellular proteins has been identified in animal studies [58,59]. The presence of HNE-modified proteins suggests that oxidative stress with lipid peroxidation also contributes to islet-cell injury [60].…”
Section: Discussionmentioning
confidence: 99%
“…Glucose, fructose and their phosphorylated derivatives (>100 mM) were found to induce mutations and apoptosis in L5178Y murine lymphoma cells in vitro [32], and glucose, glucose 6-phosphate and glyceraldehyde 3-phosphate in reactions with lysine have been shown to induce mutations and the development of apurinic and apyrimidinic sites in plasmid DNA [33,34]. These studies probably reflect the formation of reactive α-oxoaldehydes in the degradation of monosaccharides, and early-stage glycation reactions and subsequent modification of DNA to form nucleotide AGEs derived from glyoxal, methylglyoxal and other carbonyl intermediates [21].…”
Section: Dna Glycation Mutagenesis and Ner (Nucleotide Excision Repair)mentioning
confidence: 99%
“…Plasmid DNA incubated with reactive AGE products produced double strand DNA breaks and base modifications [174]. A small study of 31 type II diabetic patients in Turkey found higher AGE DNA adduct concentration in patients with diabetes compared to controls, despite the use of oral hypoglycemic drugs [198].…”
Section: Mechanisms Of Peripheral Neuropathymentioning
confidence: 99%